Event Organizer Management Strategy In Selecting Venues To Increase Visitor Interest: A Case Study Of The Flei Event By Panorama Media - Toro, Sahlan; Sulaeman, Eman; Fitriana, Rina; Fauzan, Rahman (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the event organizer’s strategic management in venue selection to increase visitor interest, using the Franchise & License Expo Indonesia (FLEI) organized by Panorama Media as a case study. Venue selection plays a crucial role in attracting visitor participation, especially in the increasingly competitive MICE industry. The research employs a descriptive qualitative approach with data collected through in-depth interviews, non-participant observation, and document analysis focusing on two main venues: Jakarta Convention Center (JCC) and Jakarta International Expo (JIExpo). The findings indicate that accessibility, strategic location, market segmentation, and supporting facilities such as parking and venue comfort are dominant factors in venue selection. Data reveals that FLEI 2023 at JCC attracted significantly more visitors than FLEI 2024 at JIExpo, highlighting the impact of venue decisions on event success. This study offers practical implications for event organizers in designing strategies based on audience demographics and preferences to enhance event effectiveness and appeal.